2005
DOI: 10.1007/s11882-005-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

Basophils and mast cells in chronic idiopathic urticaria

Abstract: Chronic idiopathic urticaria (CIU) is diagnosed in patients when urticarial eruptions recur for more than 6 weeks, and no specific cause is determined. Given that urticaria resembles the lesions induced by injection of histamine or allergen into the skin, a role for mast cells or basophils has been proposed in the generation of localized urticarial lesions. However, currently, the exact mechanisms governing regional mast cell or basophil activation are unknown. In the past decade, there has been mounting inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…A recent publication reports a difference in the FcεRI-signaling molecules in basophils and mast cells of patients with CIU that may be critical for development of urticaria. 48 In the 1990s, Lee and Kim 49 demonstrated reduced histamine release in the peritoneal mast cells of rats, when treated with sulfasalazine. Similar studies on human mast cells and basophils found the opposite, ie, that sulfasalazine enhanced IgE-induced histamine release.…”
Section: Commentmentioning
confidence: 99%
“…A recent publication reports a difference in the FcεRI-signaling molecules in basophils and mast cells of patients with CIU that may be critical for development of urticaria. 48 In the 1990s, Lee and Kim 49 demonstrated reduced histamine release in the peritoneal mast cells of rats, when treated with sulfasalazine. Similar studies on human mast cells and basophils found the opposite, ie, that sulfasalazine enhanced IgE-induced histamine release.…”
Section: Commentmentioning
confidence: 99%
“…Basophils are the rarest type of leucocytes in human peripheral blood, making up less than 0.5% of the total white blood cell count in healthy individuals. Decreased basophil numbers in patients with CSU indicate their role in the activation and function of the cells …”
Section: Introductionmentioning
confidence: 99%
“…Decreased basophil numbers in patients with CSU indicate their role in the activation and function of the cells. 4,5 CD63 is a tetraspanin normally expressed only on the membrane of the lysosomes in the inactive basophils and mast cells. Upon activation, it moves to the surface of basophils along with degranulation.…”
Section: Introductionmentioning
confidence: 99%
“…The basis for this cellular state is unknown but the spontaneous release behavior has been associated with atopy and asthma or with food allergies (May, 1976; Findlay and Lichtenstein, 1980; May and Remigio, 1982; Tung and Lichtenstein, 1982; Peters et al, 1985). In a subpopulation of patients with chronic idiopathic urticaria, one finds basophils whose responsiveness to IgE-mediated stimulation is blunted (Kern and Lichtenstein, 1976; Luquin et al, 2005; Vonakis and Saini, 2005; Vasagar et al, 2006; Baker et al, 2008). It has been proposed that changes in the expression of SHIP (SH2-containing inositol 5′ phosphatase) is associated with poor release from this type of basophil (Vonakis et al, 2007) but the precise nature of the phenotype remains unclear.…”
Section: Introductionmentioning
confidence: 99%